Unveiling the mechanism of bactericidal activity of a cecropin A-fused endolysin LNT113 - Cho, Jeongik; Hong, Hye Won; Park, Kyungah; Myung, Heejoon; Yoon, Hyunjin (International Journal of Biological Macromolecules, 2024)
Endolysins are lytic enzymes produced by bacteriophages at the end of their lytic cycle and degrade the peptidoglycan layer of the bacterial cell wall. Thus, they have been extensively explored as a promising antibacterial agent to replace or supplement current antibiotics. Gram-negative bacteria, however, are prone to resist exogenous endolysins owing to their protective outer membrane. We previously engineered endolysin EC340, encoded by the Escherichia coli phage PBEC131, by substituting its seven amino acids and fusing an antimicrobial peptide cecropin A at its N-terminus. The engineered endolysin LNT113 exerted superior activity to its intrinsic form. This study investigated how cecropin A fusion facilitated the bactericidal activity of LNT113 toward Gram-negative bacteria. Cecropin A of LNT113 markedly increased the interaction with lipopolysaccharides, while the E. coli defective in the core oligosaccharide was less susceptible to endolysins, implicating the interaction between the core oligosaccharide and endolysins. In fact, E. coli with compromised lipid A construction was more vulnerable to LNT113 treatment, suggesting that the integrity of the lipid A layer was important to resist the internalization of LNT113 across the outer membrane. Cecropin A fusion further accelerated the inner membrane destabilization, thereby enabling LNT113 to deconstruct it promptly. Owing to the increased membrane permeability, LNT113 could inactivate some Gram-positive bacteria as well. This study demonstrates that cecropin A fusion is a feasible method to improve the membrane permeability of endolysins in both Gram-negative and Gram-positive bacteria.
Keywords: Antimicrobial peptide; Bactericidal activity; Cecropin A; Core oligosaccharide; E. coli; Endolysin; Gram-negative bacteria; Lipopolysaccharides; Membrane permeability; Outer membrane; Anti-Bacterial Agents; Antimicrobial Cationic Peptides; Endopeptidases; Escherichia coli; Gram-Negative Bacteria; Gram-Positive Bacteria; Lipid A; Oligosaccharides; Antimicrobial peptide; Endolysin; Gram-negative bacteria; Lipopolysaccharide; Membrane permeability